Orientation and Conformation of Hydrophobin at the Oil-Water Interface Insights from Molecular Dynamics Simulations - Yu, Hai (Langmuir : the ACS journal of surfaces and colloids, 2022)
Hydrophobins, a new class of potential protein emulsifiers, have been extensively employed in the food, pharmaceutical, and chemical industries. However, the knowledge of the underlying molecular mechanism of protein adsorption at the oil-water interface remains elusive. In this study, all-atom molecular dynamics simulations were performed to probe the adsorption orientation and conformation change of class II hydrophobin HFBI at the cyclohexane-water interface. It was proposed that a hydrophobic dipole of the protein could be used to quantitatively predict the orientation of the adsorbed HFBI. Simulation results revealed that HFBI adsorbed at the interface with the patch-up orientation toward the oil phase, regardless of its initial orientations. HFBI's secondary structure was maintained to be intact in the course of simulations despite relatively significant variations in the tertiary structure observed, which could well preserve the bioactivity of HFBI. From the energy analysis, the driving force for interface adsorption was primarily determined by van der Waals interactions between HFBI and cyclohexane. Further analysis indicated that the adsorption orientation and conformation of HFBI at the oil-water interface were typically regulated by the hydrophobic patch and some key residues. This study provides some insights into the orientation, conformation, and adsorption mechanism of proteins at the oil-water interface and theoretical guidelines for the design and development of novel biological emulsifiers involved in the food, pharmaceutical, and chemical industries